2019
DOI: 10.1016/j.jid.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective Effects of Dietary Grape Powder on UVB Radiation-Mediated Skin Carcinogenesis in SKH-1 Hairless Mice

Abstract: Skin cancer is the most frequently diagnosed cancer in the United States, and solar UVR is an established causative factor for approximately 90% of these cases. Despite efforts aimed at UV protection, including use of sunscreen and clothing, annual cases of skin cancer continue to rise. Here, we report that dietary grape powder mitigates UVB-mediated skin carcinogenesis in an SKH-1 hairless mouse model. Using a UVB initiationpromotion protocol, whereby mice were exposed to 180 mJ/cm 2 UVB two times per week fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 40 publications
5
30
0
Order By: Relevance
“…After two weeks of GP consumption, 180 mJ/cm 2 UVB was given every other day for 2 weeks ( Figure 1 a). As previously observed [ 24 ], GP supplementation was well tolerated in all mice. The average daily GP consumption in the 5% GP group corresponded to 239.8 ± 11.3 and 197.5 ± 4.1 mg for males and females, respectively.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…After two weeks of GP consumption, 180 mJ/cm 2 UVB was given every other day for 2 weeks ( Figure 1 a). As previously observed [ 24 ], GP supplementation was well tolerated in all mice. The average daily GP consumption in the 5% GP group corresponded to 239.8 ± 11.3 and 197.5 ± 4.1 mg for males and females, respectively.…”
Section: Resultssupporting
confidence: 82%
“…Although no registries document the current incidence of NMSC cases in the US, epidemiological studies have reported that cases of NMSC are significantly higher in men than women [ 4 , 5 ]. Previously, we demonstrated the long term effects of GP consumption against UVB-mediated carcinogenesis in female SKH-1 hairless mice [ 24 ]. Here, we sought to determine the effects of GP on UVB skin carcinogenesis in male SKH-1 mice utilizing the same initiation-promotion protocol (180 mJ/cm 2 UVB twice weekly for 28 weeks) ( Figure 2 a), since it is known that males tend to produce larger skin tumors that may appear earlier compared to females, upon UVB exposure [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diet included a 0, 3, or 5% concentration of freeze-dried GP. The diet resulted in increased apoptosis and reduced lipid peroxidation and proliferative markers [ 220 ]. The treatment also increased NER-facilitated repair of the skin by reducing the level of CPDs [ 220 ].…”
Section: Role Of Whole Fruits and Vegetables In Skin Cancer Prevenmentioning
confidence: 99%
“…The diet resulted in increased apoptosis and reduced lipid peroxidation and proliferative markers [ 220 ]. The treatment also increased NER-facilitated repair of the skin by reducing the level of CPDs [ 220 ]. Overall, grapes and their components exert promising activity as naturally-occurring anti-inflammatory and anti-neoplastic agents.…”
Section: Role Of Whole Fruits and Vegetables In Skin Cancer Prevenmentioning
confidence: 99%